2022
DOI: 10.1016/j.seps.2021.101161
|View full text |Cite
|
Sign up to set email alerts
|

Trade, uneven development and people in motion: Used territories and the initial spread of COVID-19 in Mesoamerica and the Caribbean

Abstract: Mesoamerica and the Caribbean form a region comprised by middle- and low-income countries affected by the COVID-19 pandemic differently. Here, we ask whether the spread of COVID-19, measured using early epidemic growth rates ( r ), reproduction numbers ( R t ), accumulated cases, and deaths, is influenced by how the ‘used territories’ across the regions have been differently shaped by uneven development, human movement and trade differences. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…This is probably due to the fact that high GDP implies more intense international economic exchanges and consequently higher levels of global interconnection among individuals increasing the possibilities of virus transmission [ 135 ]. This is supported also by some studies which conclude that trade intensity showed a positive correlation with COVID-19 infections and deaths [ 25 , 136 ].…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…This is probably due to the fact that high GDP implies more intense international economic exchanges and consequently higher levels of global interconnection among individuals increasing the possibilities of virus transmission [ 135 ]. This is supported also by some studies which conclude that trade intensity showed a positive correlation with COVID-19 infections and deaths [ 25 , 136 ].…”
Section: Resultssupporting
confidence: 76%
“…The upturned arrow represents a positive association, the downturned stands for negative association and the horizontal bar is when no or non-statistically significant association was found. Citation Elev Long Lat Urb other Country/Region of study Territorial variable detail COVID-19 outcomes Amdaoud et al [ 21 ] X Europe Urban regions Deaths ↑ Armillei et al [ 22 ] X Italy Peripheral areas Deaths ↑ Ascani et al [ 23 ] X Italy Presence of an airport in the province Infections ↑ Boterman [ 24 ] X Netherlands Distance from train/motorway Infections ― Chaves et al [ 25 ] X Central America and Caribbean Number of international territories/cities connected through the main airport Death ↑ Chen et al [ 26 ] X Hubei (China) Distance by road from Wuhan Infections ↓ Coker et al [ 27 ] X Northern Italy Distance in meters to the closest airport Death ↑ ...…”
Section: Resultsmentioning
confidence: 99%
“…The latter networks connect what may be, in other senses, 'distant' counties into regional livestock outbreaks or-for pathogens that have already spilled over into human populations-urbanized pandemics [32,[44][45][46]. Chaves et al [47] showed that moderating certain sorts of international interconnection (whether by strategic 'delinking' [48] or unwanted peripheralization [49,50]) reduced the burden of COVID-19 in countries of Mesoamerica and the Caribbean.…”
Section: Us Midwest Covid-19 and Modes Of Agricultural Productionmentioning
confidence: 99%
“…The context of COVID-19 outcome can be expanded from public health responses to dominant modes of economic production. Across Mesoamerica and the Caribbean, clusters of countries for epidemiological variables such as the exponential growth rate, and COVID cases and deaths 100 days after detection of first case, were matched with clusters based on uneven development variables, including HDI, the WHO Universal Health Care index, and several trade indicators ( 10 ). In Mesoamerica and the Caribbean, trade openness was associated with increases in COVID cases and deaths.…”
Section: Main Textmentioning
confidence: 99%
“…Public health interventions and traditional SEIR modeling from which such campaigns often take direction must reach beyond cataloguing the emergent properties of populations of interacting individuals ( 11 ). The broader social landscapes in which pathogens evolve drive disease outbreaks ( 10, 11 ). The causes for the evolution of diseases are found as much in the field of the social determinants of health as in the object of the pathogen or patient population.…”
Section: Main Textmentioning
confidence: 99%